2018
DOI: 10.2207/qjjws.36.86
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development on the Welding Process for Reducing Diffusible Hydrogen

Abstract: Cold cracking is a serious concern in the welding of large-scale steel structures. And, diffusible hydrogen is a major factor affecting to it. Several general techniques are known for preventing cold cracking, however there are no examples of approach in the past from welding apparatus side. The new welding process was developed to reduce diffusible hydrogen content in the weld metal with special welding torch in GMAW and FCAW. Furthermore, the factors were researched that affecting the effectiveness of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, the presence or absence of seams on a wire electrode also contributes to the amount of diffusible hydrogen in a weld bead [19]. For instance, the effectiveness of Mukai et al's [20] novel welding torch for reducing diffusible hydrogen was strongly affected by the use of a seamed flux-cored wire. Ushio et al [21] observed that the effect of Ohmic heating and arc heating on the melting rate of flux-cored wire is reduced compared to the effect on the melting rate of solid wires.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence or absence of seams on a wire electrode also contributes to the amount of diffusible hydrogen in a weld bead [19]. For instance, the effectiveness of Mukai et al's [20] novel welding torch for reducing diffusible hydrogen was strongly affected by the use of a seamed flux-cored wire. Ushio et al [21] observed that the effect of Ohmic heating and arc heating on the melting rate of flux-cored wire is reduced compared to the effect on the melting rate of solid wires.…”
Section: Introductionmentioning
confidence: 99%
“…This torch was based on the results of the study on the evaporation of moisture and other hydrogen sources as well as its penetration route to the weld pool. Then, the feasibility of reducing the diffusible hydrogen content during gas metal arc welding (GMAW) and FCAW was discussed [4,14]. As a result, this torch was found to be effective for both GMAW and FCAW.…”
Section: Introductionmentioning
confidence: 99%